Voltage manipulation of desired magnetization orientation in multiferroic heterostructures. (1st March 2021) - Liu, Jiahao; Yang, Xiaokuo; Hong, Dunhua; Li, Cheng; Xu, Nuo; Yang, Binbin; Fang, Liang
Abstract: We report the pure voltage manipulation of desired in-plane magnetization orientation of the nanomagnets in Ni/PMN-PT multiferroic heterostructure and systemically studies the effect of localized stress on the magnetization orientation by magnetic force microscope. Referable analysis about the dynamic magnetization process of the nanomagnet are provided by micromagnetic simulation. Both the experiments and simulations have proved that the 180 degrees switching of the nanomagnets can be induced without strict requirements of the voltage waveform. The results can be effectively applied to electrical induced logic writing of low-energy-consumption spintronic devices. Graphical abstract: